SIAC releases new arbitration rules - REED, Lucy (Institutional Knowledge at Singapore Management University, 2013)
The Singapore International Arbitration Centre (SIAC) has released a 5th edition of the SIAC Arbitration Rules, which entered into force yesterday (1 April 2013). The new rules apply to all SIAC arbitrations commenced after 1 April unless the parties agree otherwise.